Managerial Qualifications of Personnel Occupying Overseas Management Positions as Perceived By American Expatriate Managers - Miller, Edwin L. (Journal of International Business Studies, 1977)
This study presents the results of an investigation designed to examine the perceptions of American expatriate managers held with respect to the managerial qualifications of their superiors and subordinates in overseas operations of three American multinational companies. The results of the study indicate that regional location and length of time worked overseas were related to the managers' perceptions.